Acquired Haemophilia A. Which is the best therapeutic choice in older adults? Single center study of 4 cases - Mauro, E.; Garlatti Costa, E.; Zanier, A.; Maset, M.; Ermacora, A.; Ghersetti, M.; Casarin, P. (Reumatismo, 2019)
Acquired haemophilia A (AHA) is a rare bleeding disorder due to autoantibodies directed against coagulation factor VIII. The treatment is based on recombinant activated factor VII and activated prothrombin complex concentrate. However, mainly in older patients, severe thrombotic complications have been reported. Here we report the different therapeutic approaches in 4 cases of elderly patients with AHA and co-morbidities.